2021
DOI: 10.3390/biom11060842
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Alkaline Phosphatase and Low Muscle Mass Index Among Korean Adults: A Nationwide Population-Based Study

Abstract: Sarcopenia has attracted interest due to its impact on various health problems. Chronic inflammation is an important contributor to sarcopenia. Thus, we aimed to investigate the association between serum alkaline phosphatase (ALP), which is a novel inflammatory marker, and muscle mass. This study included 15,579 adults from the 2008–2011 Korea National Health and Nutrition Survey. Low skeletal muscle mass index (LSMI) was defined as body mass index-adjusted appendicular skeletal muscle mass less than 0.789 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, higher FPG (in men aged 65–74 years) is speculated to be related to lower basal insulin secretion or possibly excessive alcohol intake, which makes elevated morning glucose positively correlated with sarcopenia among men. AST (in women aged 65–74 years) was previously reported 9 to be directly related to skeletal muscle mass. Cr (in women aged ≥75 years), which had wide CIs, and eGFR (among women) were risk factors for a positive Yubi-wakka test result.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, higher FPG (in men aged 65–74 years) is speculated to be related to lower basal insulin secretion or possibly excessive alcohol intake, which makes elevated morning glucose positively correlated with sarcopenia among men. AST (in women aged 65–74 years) was previously reported 9 to be directly related to skeletal muscle mass. Cr (in women aged ≥75 years), which had wide CIs, and eGFR (among women) were risk factors for a positive Yubi-wakka test result.…”
Section: Discussionmentioning
confidence: 95%
“…Further, we investigated the content of alkaline phosphatase, the activity of which, according to literature data, changes in skeletal muscle pathology [25]. The highest levels of alkaline phosphatase were found in children from group 1, while in patients with diabetic myopathy, its serum content was not statistically different from the control group (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the established decrease in serum content of this enzyme with the progression of structural and functional changes in skeletal muscles of children with diabetes seems logical. It is possible that an increased activity of alkaline phosphatase in patients with preserved mass and strength of skeletal muscles may be due to the development of nonspecific low-grade inflammation and oxidative stress against the background of hyperglycemia [31], which acts as a factor of skeletal muscle fibrosis [32] and a trigger for muscle loss [25]. As chronic oxidative stress progresses, alkaline phosphatase activity decreases.…”
Section: Discussionmentioning
confidence: 99%
“…High ALP levels were also associated with the development of sarcopenia in cirrhotic patients. Lee et al [32] explored the relationship between serum ALP levels and low muscle mass index in 15,579 adults in Korea, and the ndings suggested that serum ALP may serve as a marker of in ammation and a predictor of sarcopenia. Further research is needed to con rm whether ALP can predict sarcopenia development in cirrhosis patients.…”
Section: Discussionmentioning
confidence: 99%